Different thermal degradation mechanisms: Role of aluminum in Ni-rich layered cathode materials. (December 2020) - Jo, Eunmi; Park, Jae-Ho; Park, Junbeom; Hwang, Jieun; Chung, Kyung Yoon; Nam, Kyung-Wan; Kim, Seung Min; Chang, Wonyoung
Abstract: Despite increasing demands for higher energy density cathode materials, they can be bigger threats unless thermal stability is guaranteed. Herein, the thermal stability of Lix Ni0.835 Co0 . 15 Al0 . 015 O2 (NCA83) and Lix Ni0.8 Co0 . 15 Al0 . 05 O2 (NCA80) is compared by using in-situ transmission electron microscopy. Analysis demonstrates that NCA83 and NCA80 degrade thermally by distinct mechanisms. Al prevents the transition to CoO2 -type O1 phase by suppressing O-slab gliding by residual Li. At 67% SOC, in the sub-surface area, thermal degradation of NCA80 is mainly due to reduction of Ni, whereas thermal degradation of NCA83 is a result of concurrent reduction of Ni and Co. The difference indicates that NCA83 has both earlier transition to the rock-salt structure and poorer thermal stability than NCA80. This study presents a protocol to properly evaluate new high energy density cathode materials, and provides important insights into the thermal degradation mechanism of Ni-based layered oxides. Graphical abstract: Image 1 Highlights: Thermal stability of Ni-rich layered cathode materials is evaluated by using in-situ TEM. In-situ TEM analysis shows that NCA83 and NCA80 degrade thermally by distinct mechanisms. Al in NCA80 plays a role in preventing the formation of O1 phase (CoO2 ) during charging. O1 phase in charged NCA83 results in the concurrent reduction of Ni and Co and thus fast thermal degradation. The advantage in capacity cannot be fully exploited without thermal stability.